2013
DOI: 10.5204/intjfyhe.v4i2.173
|View full text |Cite
|
Sign up to set email alerts
|

Belonging in Education: Lessons from the Belonging Project

Abstract: This paper presents some preliminary findings from The Belonging Project-a longitudinal learning and teaching research project seeking to develop and define a new approach to student engagement. In this project, the concept of belonging is used as a tactic to engage both staff and students in the School of Media and Communication at RMIT University as part of the project's aim to improve the student experience. This paper maps the way in which we use belonging-defined in relation to the educational experience-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Many studies have reported that developing feelings of belonging and connection to classes facilitate students' engagement and motivation with the content and academic activities (Freeman et al, 2007;Wilson et al, 2015;Zumbrunn et al, 2014). In Australia, Morieson, Carlin, Clarke, Lukas, & Wilson (2013) have emphasised that social interactions with peers benefit the sense of belonging to a school, particularly when they are promoted in and outside classes for the academic staff.…”
Section: Benefits Of Teacher-student Interactions In Higher Educationmentioning
confidence: 99%
“…Many studies have reported that developing feelings of belonging and connection to classes facilitate students' engagement and motivation with the content and academic activities (Freeman et al, 2007;Wilson et al, 2015;Zumbrunn et al, 2014). In Australia, Morieson, Carlin, Clarke, Lukas, & Wilson (2013) have emphasised that social interactions with peers benefit the sense of belonging to a school, particularly when they are promoted in and outside classes for the academic staff.…”
Section: Benefits Of Teacher-student Interactions In Higher Educationmentioning
confidence: 99%
“…The sense of belonging with other FYTE coordinators and the ability to share weaknesses as well as effective practices and achievements were seen as essential for building their leadership capacity. As Morieson, Carlin, Clarke, Lukas, and Wilson (2013) observed, a sense of belonging is essential for staff who are seeking to encourage belonging in students. In the case of the FYE program, belonging to a community outside their faculty helped coordinators to build and sustain their local leadership in both more and less supportive local contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In higher education, belonging has been closely linked to persistence and retention (Tinto, 1993;Hurtado & Carter, 1997), and improved first-year student experiences (Kift, Nelson, & Clarke, 2010;Krause, 2005;Morieson, Carlin, Clarke, Lukas, & Wilson, 2013). In 2010, 809 Kift, Nelson and Clarke named "belonging" as one of three principles driving Queensland University of Technology"s (QUT) innovative, whole-of-institution approach to the firstyear experience.…”
Section: Introductionmentioning
confidence: 99%
“…Through a range of low cost, small-scale activities such as Cohort Day Out initiatives, coordinated Orientation Week activities and the co-creation of student informal spaces, the Belonging Project delivered a range of positive, discipline based interactions amongst student cohorts and between students and staff. Mix methods evaluation through surveys, focus groups and interviews has shown the initiatives provided a successful way to develop stronger connections amongst cohorts and significantly improved students" sense of belonging (for further discussion, see Morieson, Carlin, Clarke, Lukas, & Wilson, 2013;Araujo, Wilson, & Clarke, 2015;Clarke, & Wilson, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation